Want this question answered?
Be notified when an answer is posted
24a + b2 + 3a + 2b2= 27a + 3b2
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.
The Answer to this question is 9 (2B+4) and (1B+3)
(x + y)2 = x2 + 2xy + y2 So x2 + y2 = (x + y)2 - 2xy = a2 - 2b Then (x2 + y2)2 = x4 + 2x2y2 + y4 So x4 + y4 = (x2 + y2)2 - 2x2y2 = (a2 - 2b)2 - 2b2 = a4 - 4a2b + 4b2 - 2b2 = a4 - 4a2b + 2b2
3a(b+c)+2b(b+c)
do you mean 12a3 - 5a2b - 2b2 ?? = 12a3 + 8a2b - 3a2b - 2b2 then group 1st 2 terms and last 2 and use GCF = (12a3 + 8a2b) + ( - 3a2b - 2b2) = 4a2(3a + 2b) + (-b)(3a2 +2b) not much help, but that's all folks
(a2+2b2-2ab)(a2+2b2+2ab)
24a + b2 + 3a + 2b2= 27a + 3b2
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.
2b2 + 8 para b = -3
n nn n
3a2b(2b2-1)
Metformin
= 4a2 + 2ab 2b2
3(2b2 - 5b - 2)
11(2b2 + 21)
C. 12b3